Dual-band dual linear to circular polarization converter in transmission mode-application to K/Ka-band satellite communications - Naseri, P.; Matos, S.; Costa, J. R.; Fernandes, C. A.; Fonseca, N. J. G. (IEEE Transactions on Antennas and Propagation, 2018)
Many wireless communication applications such as satellite communications use circularly polarized (CP) signals, with the requirement for easy switching of the polarization sense between uplink and downlink. Specifically, in satellite communications, the trend is also to move to higher frequencies and integrate the receiving and transmitting antennas in one dual-band terminal. However, these simultaneous demands make the design and fabrication of the composing parts very challenging. We propose, here, a dual-band dual-linear polarization (LP)-to-CP converter that works in the transmission mode. The working principle of this polarizer is explained through an example for Ka-band satellite communications at 19.7–20.2 and 29.5–30 GHz. The LP-to-CP converter is a single panel composed of identical unit cells with a thickness of only 1.05 mm and a size of 5.3 mm ×5.3 mm. Due to its operation in the transmission mode, the polarizer can be combined with a simple dual-band dual-LP antenna to obtain the desired dual-band dual-CP single antenna. However, the unique property of this polarizer is yet the fact that it converts a given LP wave, e.g., x-polarization, to orthogonal CP waves at the two nonadjacent frequency bands, e.g., left-handed CP at lower band and right-handed CP at higher band. The polarizer is tested both with 20 and 30 GHz LP rectangular horns to illuminate a dual-band transmit array (TA) to obtain wide-angle steering of CP beams. The performance of the polarizer and its association with the TA is evaluated through simulation and measurements. We also present design guidelines for this type of polarizer.